Characterization of the salivary microbiome in healthy Thai children - Izumi Mashima (2020)
© 2019 Asian Pacific Journal of Tropical Medicine Produced by Wolters Kluwer- Medknow. All rights reserved. Objective: To investigate the composition of the salivary microbiome of 50 healthy Thai children. Methods: A total 76 provinces in Thailand are grouped into 5 geographical clusters based on unique economics, foods and lifestyles. Geographical locations and the results of an oral assessment were also considered. Genomic DNA was extracted from stimulated sdiva samples. Subsequently, amplicon libraries were prepared by 16S Metagenomic Sequencing Library Preparation. The amplicons were sequenced using an Illumina Miseq platform followed by bioinformatics and statistical analyses. Results: The correlation between oral hygiene status and caries history varied from r2=0.887 to r2=0.999 in the geographical groups, suggesting oral hygiene status a strong association between caries history. Twenty taxonomic groups were found in all subjects and constituted 93.6%-96.5% of the microbiome. Of these, genus Veillonella and Prevotella showed significant differences in their proportions between the geographical groups (P<0.05). Furthermore, the proportion of Veillonella parvula, as well as Rothia aeria and Rothia dentocariosa tended to increase with worse oral hygiene status, which was also related to higher dental caries history. Conclusions: The differences in the salivary microbiome as related to geographic regions suggest that environmental factors, which may include dietary habits, could influence the predominant bacteria found in the mouth of Thai children, especially the genus Veillonella and Prevotella. The ratio of Veillonella parvula, Rothia aeria and Rothia dentocariosa may be indicators of worse oral hygiene status and future caries in this population.